Pengaruh Visual Merchandising Dan Price Perception Terhadap Impulse Buying Dengan Positive Emotion Sebagai Variabel Mediasi Pada Konsumen Miniso Kota Padang - Nur Aina Muhgnis Tanjung; Yesi Elsandra (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of store atmosphere, visual merchandising, This study aims to analyze the effect of visual merchandising and price perception on impulse buying with positive emotion as a mediating variable among Miniso consumers in Padang City. This research employs a quantitative approach using a survey method. The population consists of Miniso consumers in Padang City, with a sample of 250 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using structural model analysis. The results indicate that visual merchandising and price perception influence impulse buying both directly and indirectly through positive emotion. Positive emotion is proven to act as a mediating variable that strengthens the relationship between external retail factors and consumers’ impulse buying behavior. This study contributes to the development of consumer behavior literature and provides practical implications for retail managers in designing product display strategies and pricing policies to enhance positive emotions and consumers’ impulse buying.